A Correlational Study Between Emotional Intelligence and Self-Esteem Among University Students in Quetta - Batool,; Hameedullah,; Naseeb Ullah,; Izzat Ullah,; Shah , Syed Adil; Kakar , Amin Ullah; Kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: In daily life, emotional intelligence, or EI, is crucial. Humans must engage in a variety of social activities and interact with others on a regular basis since they are social creatures. To communicate effectively and constructively, one must be able to control their emotions as well as comprehend those of others. Objective: To examine relationship between emotional intelligence and self-esteem determine if there are any differences in emotional intelligence and self-esteem levels between male and female students. Methods: The study was conducted to investigate the relationship between emotional intelligence (EI) and self-esteem among university students of Quetta. Correlational research design was used for the present study to examine the relationship between emotional intelligence and self-esteem. Results: The result indicates non-significant mean difference on Schutte Self-Report Emotional Intelligence Scale with t (248) = -1.42, p ˃ .05 on female students. Findings revealed that female students exhibited higher scores on SSEIT as compared to male students. The value of Cohen’s d was 0.18 which indicated small effect size. Furthermore, results also indicated non-significant mean difference on RSE t (248) = .1.56, p ˃ .05 on male students and revealed that male students exhibited higher self-esteem as compare to female students. The value of Cohen’s d was 0.19 which indicated small effect size. Conclusion: The above table demonstrates the predictive influence of Emotional Intelligence on Self-Esteem. The result shows significant influence of Emotional Intelligent on Self-Esteem at university level (p <.001). The table indicates Emotional Intelligence predict Self-Esteem strongly as 4.9% of the total variance in Self-Esteem score (R2= .049, F= 12.822, p <.000).